Evaluation of the redox alteration in Duchenne muscular dystrophy model mice using in vivo DNP-MRI - Hinako Eto; Masaharu Murata; Takahito Kawano; Yoko Tachibana; Abdelazim Elsayed Elhelaly; Yoshifumi Noda; Hiroki Kato; Masayuki Matsuo; Fuminori Hyodo (npj Imaging)
Abstract Duchenne muscular dystrophy (DMD) is a genetic muscular disease and is the most common type of muscular dystrophy in Japan. Noninvasive magnetic resonance imaging (MRI) can be used for follow-up evaluation of myositis and muscular dystrophy, including DMD and inflammation is evaluated based on the increased muscle water as evaluated by T2-weighted MR images. However, in MDM, the redox status has not been evaluated non-invasively during the disease progression. We assessed the inflammation via the redox status in experimental animal disease models using in vivo dynamic nuclear polarization MRI (DNP-MRI) with a redox probe. The current study aimed to evaluate the skeletal muscle of mdx mice, a DMD model, in which muscle fiber necrosis, inflammation, and muscle regeneration were chronically repeated. Results showed that the reduction rate of Carbamoyl-PROXYL (CmP), one of the redox probes, radicals in mdx mice increased compared with that in normal mice. In vitro, more mitochondria or macrophages enhanced the radical form decay reaction by reducing CmP. Due to muscle fiber damage, the mdx mice had a lower mitochondrial concentration in the gastrocnemius muscle than the normal mice. However, the in vivo DNP-MRI results strongly reflected the increased reduction of CmP radicals by macrophages. In conclusion, in vivo DNP-MRI, a noninvasive imaging method is useful for locally evaluating skeletal muscle inflammation.